A case of cavernosal abscess after neglected penile fracture and bacteremia - Lazaros Lazarou; Marinos Berdempes; Titos Markopoulos; Nikolaos Kostakopoulos; Konstantinos Spyropoulos; Iraklis C Mitsogiannis (Urology Annals, 2019)
Penile abscess is a urological entity rarely described in the literature. It has been associated with injection therapy for erectile dysfunction, penile instrumentation, trauma and priapism. Identified risk factors include immunosuppresion and pre-existing local or distant infection. Common causal microorganisms include Staphylococcus aureus, Streptococci and Bacteroides. We herein report on a case of penile abscess in a 37-year-old patient occurring after sexual trauma and presenting with bacteremia.